2015
DOI: 10.1007/s13277-015-3147-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation level of OPCML and SFRP1: a potential diagnostic biomarker of cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a malignancy of the bile duct epithelium which is caused by liver fluke infection. The clinical symptoms of CCA were revealed as the disease progresses to advanced stage. Thus, specific diagnostic biomarkers are important for this fatal disease. We applied methylation-sensitive high-resolution melting (MS-HRM) to quantify DNA methylation levels of opioid binding protein/cell adhesion molecule-like gene (OPCML) and Secreted frizzled-related protein 1 (SFRP1) in 73 primary CCA and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In order to overcome the low sensitivity, other biomarkers could be added to the panel. A recent study identified DNA methylation level of OPCML and SFRP1 as a potential diagnostic biomarker in BTC [58]. The AUC value of OPCML was 0.932 and of SFRP1 was 0.951.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome the low sensitivity, other biomarkers could be added to the panel. A recent study identified DNA methylation level of OPCML and SFRP1 as a potential diagnostic biomarker in BTC [58]. The AUC value of OPCML was 0.932 and of SFRP1 was 0.951.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy using such HRMG showed superior diagnosis (73%‐91%) and high specificity (95%‐100%) compared to the conventional cytology test (58%‐63%). Recently, additional HRMG with high performance have been identified, including SFRP1 , OPCML and SHOX2 (Table ), and additional optimization of the HRMG analyses may yield further improvements in performance.…”
Section: Clinical Decision By Combination Of Highly Relevant Methylatmentioning
confidence: 99%
“…7 In addition to their role in transcription silencing and tumor development, the hypermethylation of promoters at specific CpG sites can be sensitive and specific diagnostic and prognostic markers. 8,9 For example, DNA promoter methylation of glutathione S-transferase pi 1 (GSTP1) and O-6-methylguanine-DNA methyltransferase (MGMT1) is reported as a potential diagnostic marker for glioblastoma and prostate cancer. [10][11][12] It has been shown that 95% of the adenocarcinoma of the prostate have methylated GSTP1 promoter, while the normal tissues were apparently negative.…”
Section: Introductionmentioning
confidence: 99%